STUDI TEOLOGIS MENGENAI RELASI ANTARA POSISI DAN PENGARUH DALAM KEPEMIMPINAN KRISTEN - Setiadarma, Ferijanto (SEKOLAH TINGGI TEOLOGI DAN ENTREPRENEURSHIP PRINGGADING (STEP) SEMARANG, 2023)
Leadership, both in general and Christian, has many important aspects. Two of them are aspects of position and influence. Leadership positions are indeed important as long as they are achieved in the right way and at the right time and do not exercise leadership through arrogance or abuse of authority. However, position does not immediately give rise to the influence of an effective leader. Position only relates to power that is limited to that position. On the other hand, the influence of an effective leader can extend even if that person does not have any position in the institution or organization where he works or serves. The aim of this research is to try to see whether there is a relationship between the two aspects so that they can be placed in the correct proportion.